National Character Does Not Reflect Mean Personality Trait Levels in 49 Cultures - Terracciano, Antonio (Array, 2005)
Most people hold beliefs about psychological characteristics typical of members of their own and others' cultures. These perceptions of national character may be generalizations from personal experience, or stereotypes with or without a “ kernel of truth." We obtained national character ratings from 49 cultures and compared them to average personality scores of culture members as assessed by observer ratings and self-reports. National character ratings appeared to be reliable and valid measures, but they did not converge with assessed personality traits. Perceptions of national character thus appear to be unfounded stereotypes that may serve the function of maintaining a national identity.